Mathematics anxiety in schools: An analysis of causes and possible strategies based on evidence from teachers and students - Anneke Primadiana; Bambang Avip Priatna Martadiputra; Tatang Herman (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2026)
Mathematics anxiety is a psychological condition that affects students’ learning processes and is characterized by feelings of anxiety, tension, or fear when dealing with mathematics. This study aims to analyze the causes of students’ mathematics anxiety and identify possible strategies to address it based on evidence from students and teachers. This research employed a qualitative approach with a case study design, supported by descriptive data from a mathematics anxiety questionnaire. The participants were 39 students from Class XI F at SMAN 17 Bandung, with six students selected for interviews based on their anxiety levels. Data were collected through the Mathematics Anxiety Rating Scale (MARS) questionnaire, semi-structured interviews with students and teachers, and classroom observations. The questionnaire data were analyzed descriptively, while interview and observation data were analyzed thematically. The results showed that 66.67% of students experienced moderate anxiety, 25.64% experienced low anxiety, and 7.69% experienced high anxiety. The dominant indicator was cognitive disturbance at 59%, followed by negative attitudes toward mathematics at 58% and somatic symptoms at 54%. The factors causing mathematics anxiety included internal factors, such as insufficient mastery of prerequisite material, learning style, and fear of making mistakes, as well as external factors, such as fast-paced learning, curriculum pressure, peer competition, and parental expectations. The possible strategies to reduce mathematics anxiety include cognitive support through self-regulated learning and heterogeneous group learning, emotional support through positive affirmation and collaborative learning, and pedagogical adaptations through multimodal learning, remedial instruction, and constructivist approaches. These findings highlight the importance of integrating psychological and pedagogical support to reduce mathematics anxiety in school mathematics learning.